Detection of the largest herd of dugongs (Dugong dugon) in the Central Arabian Gulf using unmanned aerial vehicles - Alagha, Danah I.; Soliman, Yousria; Marshall, Christopher; Alansi, Mehsin (Frontiers in Marine Science, 2025)
The dugongs (Dugong dugon), one of the few marine herbivorous mammals, are classified as vulnerable species by the IUCN, and their population monitoring is critical for informed conservation efforts. Although limited research has confirmed that the Arabian Gulf, in the northwest Qatar, hosts the world’s largest dugong aggregations, studies on their exact numbers remain limited. We conducted boat-based drone surveys in 2019–2020 to estimate the magnitude of the sizable aggregations of dugongs in northwest Qatar. We conducted 14 surveys during 2019–2020 by employing Unmanned Aerial Vehicle (Drone) and photographic analysis techniques. Potential biotic and abiotic factors driving this gathering of dugongs were explored. Maximum dugong observed counts were 1108 in 2019 and 1209 in 2020. The percentage of cow-calf pairs in the total group was 5.8% in 2019, and 10.2% in 2020. Upon applying a detection probability of 0.96 and an availability probability range of 0.8-0.98, the adjusted estimated counts of dugongs ranged from 994 to 1574, with an overall estimated mean of 1248 ± 122 dugongs. We suggest that the significant dugong aggregations in the area during winter are primarily due to foraging on the abundant seagrass in this area, the relatively warmer waters (>18 °C) and the sheltering effect topography from turbulent waters caused by shamal winds during the winter months. This information is crucial for wildlife managers, stakeholders, and government agencies to facilitate informed decision-making concerning the management and protection of dugongs.